Effect of Signature Welcome Drink Presentation on Guests' Revisit Intention at Aston Nagoya City Hotel Batam - Fadilla Nofrianti; Lise Asnur (Journal of Education and Teaching Learning, 2026)
This study aimed to examine the effect of the Signature Welcome Drink Presentation on guests' revisit intention at Aston Nagoya City Hotel Batam. A quantitative survey approach was employed involving 100 respondents selected through purposive sampling. Data were collected using a validated and reliable questionnaire and analyzed using descriptive statistics, simple linear regression, the coefficient of determination (R²), and the t-test with IBM SPSS Version 26. The findings revealed that the Signature Welcome Drink Presentation had a positive and significant effect on guests' revisit intention, as indicated by the regression equation Y = 9.075 + 0.257X, a t-value of 5.372, and a significance level of 0.000 (p < 0.05). The coefficient of determination (R²) of 0.227 indicates that the Signature Welcome Drink Presentation explains 22.7% of the variance in revisit intention, while the remaining 77.3% is influenced by other factors. These findings suggest that improving the quality of the signature welcome drink presentation can serve as an effective strategy to enhance guests' experiences and encourage repeat visits.